Assessment of the potential contribution of the highly conserved C‐terminal motif (C10) of Borrelia burgdorferi outer surface protein C in transmission and infectivity. Issue 2 (3rd February 2014) - Earnhart, Christopher G.; Rhodes, DeLacy V. L.; Smith, Alexis A.; Yang, Xiuli; Tegels, Brittney; Carlyon, Jason A.; Pal, Utpal; Marconi, Richard T.
Abstract OspC is produced by all species of the Borrelia burgdorferi sensu lato complex and is required for infectivity in mammals. To test the hypothesis that the conserved C‐terminal motif (C10) of OspC is required for function in vivo, a mutant B. burgdorferi strain (B31::ospCΔC10) was created in which ospC was replaced with an ospC gene lacking the C10 motif. The ability of the mutant to infect mice was investigated using tick transmission and needle inoculation. Infectivity was assessed by cultivation, qRT‐PCR, and measurement of IgG antibody responses. B31::ospCΔC10 retained the ability to infect mice by both needle and tick challenge and was competent to survive in ticks after exposure to the blood meal. To determine whether recombinant OspC protein lacking the C‐terminal 10 amino acid residues (rOspCΔC10) can bind plasminogen, the only known mammalian‐derived ligand for OspC, binding analyses were performed. Deletion of the C10 motif resulted in a statistically significant decrease in plasminogen binding. Although deletion of the C10 motif influenced plasminogen binding, it can be concluded that the C10 motif is not required for OspC to carry out its critical in vivo functions in tick to mouse transmission.